Implementation of Thursday Habituation Nyanding Wawangi in Maximizing Students' Potential (Case Study at SMPN 3 Cibatu Purwakarta Regency) - Dewi Ratnaningsih; Selasih Margi Susanti; Suharyanto Soro; Nana Herdiana Abdul Rahman (Global Education Journal, 2025)
The application of character strengthening based on local wisdom to deal with moral degradation and lack of social sensitivity is one of the vocal points. The purpose of this study is to find and analyze the implementation of the Nyanding Wawangi Thursday habituation program in maximizing the potential of SMPN 3 Cibatu students. Researchers of qualitative research paradigm with a case study approach. The data collection method was carried out through participatory observation, in-depth interviews, and documentation studies. The data analysis technique uses an interactive model that includes data condensation, data presentation, and conclusion drawn. Sample selection was carried out by purposive sampling. The results of the study show that the implementation of Thursday Nyanding Wawangi can maximize the potential of students. In other words, this habituation based on local wisdom has succeeded in becoming a catalyst for the development of students' character and full potential, validating the important role of Sundanese local wisdom in national education.